Total endoscopic stapes surgery: Systematic review and pooled analysis of audiological outcomes. (30th September 2019) - Hall, Andrew C.; Mandavia, Rishi; Selvadurai, David
Abstract : Objective: This study evaluates the current evidence base for total endoscopic stapes surgery, specifically to establish current efficacy and safety of the technique within clinical practice. Data Sources: A systematic review of the literature on endoscopic stapes surgery was performed according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis checklist. A comprehensive search of PubMed, Embase, and the Cochrane Central Register of Controlled Trials database for relevant publications for all available dates with appropriate Medical Subject Headings search criteria in January 2018. Study Selection: Out of the 160 articles identified in the search, 14 met the inclusion criteria for further analysis. Four of these were level III and 10 level IV evidence. Data Extraction: A pooled patient population of 314 individuals was analyzed. Data Synthesis: Documented postoperative air bone gap closure to within 20 dB was found in 95.3% of individuals (285 patients). Facial nerve palsy (temporary) occurred in three patients (0.6%), with all recovering. No total sensorineural hearing losses were recorded, but two moderate sensorineural hearing losses occurred (0.6%). Perilymph fistula was noted on four occasions (1.3%). Chorda tympani trauma was documented in 3.5% of cases, with taste disturbance documented in 13 patients (5%). Conclusions: Our pooled analysis uses the current published evidence to establish the complication rate and audiological outcome for the endoscopic approach to stapes surgery. These outcomes are comparable to those documented in traditional use of the microscope for stapedectomy. Laryngoscope, 130:1282–1286, 2020